Dual/Multi-Modal Image-Guided Diagnosis and Therapy Based on Luminogens with Aggregation-Induced Emission - Linlin Zhu; Wenbo Wu (Molecules, 2024)
The combination of multiple imaging methods has made an indelible contribution to the diagnosis, surgical navigation, treatment, and prognostic evaluation of various diseases. Due to the unique advantages of luminogens with aggregation-induced emission (AIE), their progress has been significant in the field of organic fluorescent contrast agents. Herein, this manuscript summarizes the recent advancements in AIE molecules as contrast agents for optical image-based dual/multi-modal imaging. We particularly focus on the exceptional properties of each material and the corresponding application in the diagnosis and treatment of diseases.